2022
DOI: 10.1039/d2cp04249e
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of phytochrome chromophore models: an XMS-CASPT2 study

Abstract: Phytochromes are a superfamily of photoreceptors that harbor linear tetrapyrroles as chromophores. Upon light illumination, the linear tetrapyrrole chromophore undergoes a double bond isomerization which starts a photocycle. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…We also calculated the spectra for the Pr state of RcaE based on the previous quantum mechanics/molecular mechanics (QM/MM) model ( 40 ). Although the calculated spectra were blue-shifted from the experimental absorption maximum as reported in other studies ( 14 , 41 ), our calculated spectra successfully reproduced a large absorption shift between Pg and Pr peaks (67 nm, 0.30 eV) ( Fig. 3B and text S2).…”
Section: Resultssupporting
confidence: 80%
“…We also calculated the spectra for the Pr state of RcaE based on the previous quantum mechanics/molecular mechanics (QM/MM) model ( 40 ). Although the calculated spectra were blue-shifted from the experimental absorption maximum as reported in other studies ( 14 , 41 ), our calculated spectra successfully reproduced a large absorption shift between Pg and Pr peaks (67 nm, 0.30 eV) ( Fig. 3B and text S2).…”
Section: Resultssupporting
confidence: 80%
“…From a truncated model consisting of only two pyrrole rings, the effects of clockwise and anticlockwise rotations and substitution have been studied. 38 Here, it has been observed that one bond flip becomes a preferred mechanism over hula twist upon carbonyl substitution. Minimal effects of alkyl group substitution were also observed.…”
Section: Introductionmentioning
confidence: 95%
“…The CMS-PDFT method gives the correct topology of closely spaced PESs at and near conical intersections. CMS-PDFT may be compared to extended multistate complete active space second-order perturbation theory (XMS-CASPT2), , which has been demonstrated to be a highly accurate quantum chemical method that can describe important dynamic correlation effects at and near the conical intersections that control quenching and other electronically nonadiabatic processes. Although CMS-PDFT gives results of comparable quality, including near conical intersections, it is advantageous as it is much less expensive.…”
Section: Introductionmentioning
confidence: 99%